Waterfall Model Inventory Information System at Alvinda Store Karawang - Herlina Ferliyanti; Maman Abdurahman; Tri Haryati; Al Ghazali; Ayu Azizah (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Stock name is a process for calculating incoming and outgoing goods by inventory bookkeeping records. Manual calculations will take a very long time, and the risk of error is very high, so the presentation of the inventory report is hampered because it does not match the predetermined time. The stock opname information system with the Waterfall method can make it easier to accurately calculate the amount of stock inventory and can minimize the counting time to be faster. So that inventory reports can be generated quickly, accurately and on time.